Association between genetic variants in hsa-miR-27a and hsa-miR-146a gene and male infertility - Dobrijević, Zorana; Rajovski, Srećko; Matijašević Joković, Suzana; Milanović, Nikoleta; Radovanović, Nemanja; Brkušanin, Miloš; Savić-Pavićević, Dušanka; Brajušković, Goran (Journal of Medical Biochemistry, 2024)
Background: miRNAs have enormous potential to be used as diagnostic and prognostic markers as well as therapeutic targets in male infertility and diseases of the reproductive system. The aim of this study was to investigate the association between the two functional genetic variants in the hsa-miR-27a (rs2910164) and hsa-miR-146a gene (rs895819) and male infertility in North Macedonian population, as well as to test their association with the values of major seminal parameters. Methods: The case group included in this study comprised 158 men initially diagnosed with idiopathic male infertility. The control group included 126 age-matched healthy male volunteers who fathered at least one child. Results: We report for the first time the association of rs2910164 minor allele C with the increased susceptibility to asthenoteratozoospermia. Additionally, our results indicating the association of allele C with low sperm vitality are a novel finding. We did not demonstrate the association between genetic variant rs895819 and the risk of different types of male infertility. Still, the number of participants with CC genotype in subjects diagnosed with asthenoteratozoospermia was null, while in controls it reached 7.2%. We further detected the rs895819 genotype-dependent difference in rapid progressive sperm motility. Conclusions: The association of rs2910164 and rs895819 with idiopathic male infertility in general is unlikely. However, both of these variants show association with certain types of male infertility and with sperm abnormalities, which need to be confirmed in later studies in different ethnic groups.
Keywords: male infertility; rs2910164; rs895819; polymorphism; miR-27a; miR-146a